2013
DOI: 10.1007/s11832-012-0479-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and gender differences of slipped capital femoral epiphysis in the Netherlands from 1998–2010 combined with a review of the literature on the epidemiology of SCFE

Abstract: Purpose The incidence of slipped capital femoral epiphysis (SCFE) among children living in the Netherlands has never been published. Methods The national hospitalization registration system of the Netherlands was searched for the incidence of surgical procedures for SCFE in the Netherlands among different pediatric age groups between 1998 and 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 17 publications
0
21
2
1
Order By: Relevance
“…A more severe slip is associated with increased pain and a further limitation in the range of motion [ 18 , 21 , 22 ]. Epidemiological data for SCFE from different countries have been presented, but only a few are based on a total national population [ 2 , 23 26 ]. The incidence reported is related to ethnicity and sex.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more severe slip is associated with increased pain and a further limitation in the range of motion [ 18 , 21 , 22 ]. Epidemiological data for SCFE from different countries have been presented, but only a few are based on a total national population [ 2 , 23 26 ]. The incidence reported is related to ethnicity and sex.…”
Section: Introductionmentioning
confidence: 99%
“…A seasonal variation has also been described but with uncertainty concerning the role in the ethiology of SCFE [ 2 , 27 32 ]. A male-to-female ratio between 1.1:1 and up to 4.1:1 has been reported [ 1 , 2 , 23 , 25 , 28 , 33 , 34 ]. Previous reports with a total national population are based on data from national registers, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Witbreuk et al 1 reported the Dutch incidence of 11.6 per 100 000 children aged between five and 19 years of age. Interestingly, whilst there was no significant difference in gender, the number of affected female children was found to be increasing.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, incidence rates vary between studies and by geographical location. 1-9 The exact pathophysiological mechanism is widely reported and multifactorial. 1-9…”
Section: Introductionmentioning
confidence: 99%